2015
DOI: 10.1371/journal.pone.0132159
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Magnetic Resonance Imaging and Histopathological Correlates in Two SOD1 Transgenic Mouse Models of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a progressive and fatal disease due to motoneuron degeneration. Magnetic resonance imaging (MRI) is becoming a promising non-invasive approach to monitor the disease course but a direct correlation with neuropathology is not feasible in human. Therefore in this study we aimed to examine MRI changes in relation to histopathology in two mouse models of ALS (C57BL6/J and 129S2/SvHsd SOD1G93A mice) with different disease onset and progression. A longitudinal in vivo analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…These decreases correlated with axonal count in most WM regions. Interestingly, in the case of the 129Sv SOD1G93A mice the ad was reduced compared with the wild‐type mice prior to onset of the disease, whereas in the C57 SOD1G93A mice this occurred only at advanced stage of the disease . This was the first diffusion MRI study to demonstrate the differences in the time course of the axonal degeneration of motor neurons in these two strains of SOD1 mice.…”
Section: Applications Of Diffusion Mri For Studying Sc Microstructurementioning
confidence: 82%
“…These decreases correlated with axonal count in most WM regions. Interestingly, in the case of the 129Sv SOD1G93A mice the ad was reduced compared with the wild‐type mice prior to onset of the disease, whereas in the C57 SOD1G93A mice this occurred only at advanced stage of the disease . This was the first diffusion MRI study to demonstrate the differences in the time course of the axonal degeneration of motor neurons in these two strains of SOD1 mice.…”
Section: Applications Of Diffusion Mri For Studying Sc Microstructurementioning
confidence: 82%
“…Previous studies have proposed AD and RD as presymptomatic MRI markers for axonal damage and demyelination in ALS SC . Our studies have shown that RD progressively increases from the presymptomatic stage (P80) [YFP,G93A‐SOD1 group = (3.2 ± 0.8) × 10 −4 mm 2 /s versus YFP group = (3.7 ± 0.7) × 10 −4 mm 2 /s] ( p < 0.02) to the symptomatic stage (P120) [YFP,G93A‐SOD1 group = (3.3 ± 0.7) × 10 −4 mm 2 /s versus YFP group = (3.9 ± 0.6) × 10 −4 mm 2 /s] ( p < 0.004) (Figure a).…”
Section: Resultsmentioning
confidence: 54%
“…The study of AD to measure axonal damage in ALS has been elusive because of the numerous different and contradictory results reported between animal models (decreased AD) and human studies (no significant changes in AD) . In that context, our data suggested that AD showed a decrease in values in the mutant group compared with controls, particularly at the presymptomatic stage (Figure c).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…All images (T2w and T2 maps) were aligned to the same mouse brain template that was built ad hoc for this experiment, allowing a serial processing of the subjects. Moreover, although we were working at a lower field strength (4.7 vs. 7 T) than Caron et al , and hence achieving a lower signal‐to‐noise ratio, we could detect a similar trend toward increase of the T2 relaxation time of the facial and trigeminal nuclei in SOD1(G93A) mice. The absolute values of T2 relaxation time are indeed different (as the B0 filed increases, the T2 shortens), but the measured trend from the presymptomatic phase to the end stage of the disease is similar .…”
Section: Discussionmentioning
confidence: 52%